PERKEMBANGAN SOSIAL ANAK DIMASA PANDEMI DI TAMAN KANAK-KANAK AISYIYAH BALAI TALANG, KABUPATEN LIMAPULUH KOTA - Izzati Izzati; Anggi Dwi Putri (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2021)
ABSTRACT Early childhood is a time when aspects of child development develop rapidly and need to be stimulated appropriately in order to develop optimally. One aspect of child development that needs to be stimulated from an early age is the aspect of social development. Social development can be applied with other people, cooperating with others, adjusting to existing rules, ways of socializing with people who are bigger, smaller or the same age and others. At this time the social development of children cannot be optimally stimulated due to the Covid-19 outbreak, so the learning process carried out during early childhood is a time when aspects of child development develop very rapidly and need to be stimulated appropriately in order to develop optimally. One aspect of child development that needs to be stimulated from an early age is the aspect of social development. Social development can be applied with other people, cooperating with others, adjusting to existing rules, ways of socializing with people who are bigger, smaller or the same age and others. At this time, children's social development cannot be optimally stimulated due to the Covid-19 pandemic, so the learning process is carried out in a short time. The purpose of this study is to describe how the social development of children during a pandemic in Aisyiyah Balai Talang Kindergarten, Guguak District, Limapuluh Kota Regency, while the specific objective is to describe how the form of learning is to stimulate children's social development where the pandemic and the efforts of teachers in stimulate the social development of children during a pandemic. The method used in this research is qualitative research methods, namely descriptive qualitative, this research was conducted at Aisyiyah Balai Talang Kindergarten from March to April 2021. The results of this study were that during the pandemic period, the implementation of learning in stimulating the social development of children in Aisyiyah Balai Talang Kindergarten did not work effectively due to the limited learning time, the use of less varied learning methods and media so that children quickly felt bored with learning, and stimulation of social development that was not optimally stimulated during pandemic learning.